Keluarga, Pergaulan dan Pasangan Hidup: Kajian Biblika Tentang Orang Muda Dalam Surat-Surat Paulus - Joy Sopater Wasiyono (Sekolah Tinggi Teologi Paulus Medan, Sumatra Utara, 2023)
Youth is one of the backbone of the church today. Sustainability of Christian youth generation who fear God and love Him is something that should be struggled. St. Paul, the apostle of nations, is an apostle who cares for young generation. His proximity and mentoring method for Timothy prove it. Through his letters both personal to Timothy and Titus, as well as in the letters to the churches, he gives a lot of advices to be considered by the Christian youth today. This paper raises the letters of St. Paul as a source of Paul’s theology in relation to young man. There are three important aspects raise in this paper: 1) Youth and family, 2) Youth and social intercourse, 3) Youth and his/her life partner. The first section provides a review of how young man should be primarily to his parents. The second part reviews of the attitudes in social intercourse. The third part reviews of the rules and norms from St. Paul to choose a spouse and moral ethics to walk on relationship before marriage. The third part gives a big portion to discuss the values of love in a relationship before marriage.